Agile approach as an answer to internal uncertainty: a case study in large-scale manufacturing - Özgen, A.; Gençer, M. (Inderscience Publishers, 2023)
The success of agile product development in the software industry has attracted the attention of new product development (NPD) community. Agile approach has the potential to overcome the uncertainty that dominates today’s business conditions. However, there is little research regarding the performance of agile practices, most of which were developed in the software industry, in other contexts. Through a case study methodology, we explore how agile practices address organisational uncertainty in a large-scale manufacturing firm. The study, based on semi-structured interviews, covers two NPD projects with a total of 12 sub-teams. Our results indicate that in a large organisation, internal sources of NPD uncertainty dominate external sources. The three factors in organisational uncertainties are interdependency, team volatility and distributed teams. Furthermore, we develop a model to explain how various agile practices can provide the NPD teams with capabilities to mitigate these organisational uncertainties. Copyright © 2023 Inderscience Enterprises Ltd.
Keywords: Agile Practices; Large-Scale Organisation; New Product Development; Organisational Change; Uncertainty; Software Engineering; Agile Approaches; Agile Practices; Large-Scale Manufacturing; Large-Scale Organization; Large-Scales; New Product Development; Organisational; Organizational Change; Software İndustry; Uncertainty; Product Development